Who am I? - Christensen, Nancy; Barnes-Murphy, Rowan (New York : Scholastic, 1993)
Rhyming text provides clues about the nature of the animal who is speaking.
"Cartwheel Books."
Keywords: Animals -- Fiction; Literary recreations; Stories in rhyme